First evidence of Equus asinus L. in the Chalcolithic disputes the Phoenicians as the first to introduce donkeys into the Iberian Peninsula - Cardoso, João Luís (2013)
Two equid species have been documented in the Pleistocene of the Iberian Peninsula, the horse Equus caballus, and the Eurasian hemione Equus hydruntinus. While the former survived the HoloceneePleistocene until now, the timing for the extinction of the latter is unclear. Scarce, fragmented archaeological remains assess the presence of small equids living in the Holocene of Iberia. Those could possibly correspond to the Eurasian hemione although unambiguous morphological identification is often not possible. With the find of an equid tooth from Leceia, a Chalcolithic fortified site in Portugal, and using both morphological and mitochondrial genome analyses, we demonstrate for the first time the presence of a new equid species in Holocene Iberia, namely a donkey (Equus asinus). Radiocarbon dating of the tooth to Cal 2340e2130, and 2080e2060 BC with 95% probability, demonstrates that donkeys were present in Iberia well before the arrival of Phoenicians in the first quarter of the first millennium BC (900 e750 years BC), which were considered so far as the first who introduced donkeys in the region.